HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KECEMASAN PADA PASIEN KANKER PAYUDARA (CA MAMMAE) - Ratih Krisna Nurpeni (Coping: Community of Publishing in Nursing, 2014)
Breast cancer is one of the most disease that attacting female and become the first first rank of patients in all hospital in Indonesia is as much as 16,85 %. Patients with cancer will experience pshycological distress after cancer diagnosis. Family support in terms of motivating and minimize anxiety due to hospitalization is very important in supporting the fulfillment of physical and emotional needs of the patient during the hospitalization. Goal; To determine the relationship of family support with anxiety levels in patient with breast cancer in Angsoka III of Sanglah Hospital Centre Denpasar. Method; a descriptive correlational with cross-sectional approach. Sampling using purposive sampling with a total sample of 60 respondents. The research instruments used questionnairs HARS and family support. Data were analysis by using bivariate analysis with Rank Spearman analysis and showed the value of count r - 0,0493 and (p 0,000) < 0,05, which means that there is a moderate relationship with the direction of the negative relationship between family support with anxiety levels in patients of breast cancer. Conclusion; there is a relationship of family support with anxiety levels in patient with breast cancer in Angsoka III of Sanglah Hospital Centre Denpasar.